Study guides

Q: What is 7 square root of 3 plus 6 square root of 3?

Write your answer...

Submit

Related questions

300*square root of 3 + 300*square root of 6 = 1254.462165

15

14.777

Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3

Square root of 6 = 2.44948 Sq root of 6 + Sq root of 6 = 2.44948 + 2.44948 = 4.89896

It is sqrt(3)*[1 + sqrt(2)]/3 or [1 + sqrt(2)]/sqrt(3)

1+root 6 -n=3 n=1+ root 6 - 3 n=root6 -2

Square root of 6

54

No because the answers are 6 and 4 respectively.

(2√24) / √54 = (2√4√6) / (√9√6) = (4√6)/(3√6) = 4/3

square root 6

36

square root of 36 plus 10=6+10 , since square root of 36 =6=16Answer : 16

x2 - 6x + 1 = 0 x = [-(-6) +&- square root of [(-6)2 - 4(1)(1)]]/2(1) x = (6 +&- square root of 32)/2 x = [6 +&- 4(square root of 2)]/2 x = 3 +&- 2(square root of 2) x = 3 + 2(square root of 2) or x = 3 - 2(square root of 2) Check:

Example: The square root of 54 The square root of 54 is not an integer, since 54 is not a perfect square. The square root of 54 will be between 7 and 8, since 54 is between 49 and 64. Since 54 is closer to 49 than it is to 64, the square root will be closer to 7 than 8. I'd estimate the square root of 54 to be approximately 7.35 The actual square root is plus or minus 7.3484692 To simplify a square root, search for any factors greater than one that are perfect squares. Since 54 = 9 x 6, the square root of 54 equals the square root of 9 x 6 equals the square root of 9 times the square root of 6. The square root of 9 is 3, so the square root of 54 simplified is 3 times the square root of 6.

the square root of 6 is 36 or it is 3 depending on what you mean 6 SQUARED is 36 the SQUARE ROOT is 3

It is 49*sqrt(2).

x²+6x+9=49 x²+6x-40=0 x1=-6/2 - Square root of ((6/2)²+40) x1=-3 - 7 x1= -10 x2=-6/2 + Square root of ((6/2)²+40) x2=-3 + 7 x2= 4

the square root of 3, the square root of 5, the square root of 6, the square root of 7, the square root of 8 etc

X = -1 or +3.

== ==

It is 5/6*sqrt(3).

The square root of 49 is +7 OR -7 So the answers are -65/6 and 71/6 or -6.8333... and 7.1666...

Because questions can't use punctuation the question is ambiguous. Two possible interpretations of the question, with answers are given below:sqrt(3) + sqrt(6) / sqrt(2) = sqrt(3) + sqrt(6/2) = sqrt(3) + sqrt(3) = 2*sqrt(3)The more likely question is:[sqrt(3) + sqrt(6)]/sqrt(2)Multiply numberator and denominator by sqrt(2) to give[sqrt(2)*sqrt(3) + sqrt(2)*sqrt(6)]/[sqrt(2)*sqrt(2)]=[sqrt(2)*sqrt(3) + 2*sqrt(3)]/2 since sqrt(2)*sqrt(2) = 2= sqrt(3)*[sqrt(2)+1]/2AnswerSquare root three plus square root six is square root 9 over square root two. But nine can be factored out to a perfect three so you would have 3 over square root two.